Letter (copy) - Lizaso, Jose I. de
011-0075-001 COPY (MISS MCDONALD HAS ORIGINAL) Autonomous Government of Euzkadi London Delegation, Spanish Embassy, 24, Belgrave Square, S.W.1. 24th June 1937. Dear Sir Walter, At this time when the onslaught against the Basque people has culminated in the taking of Bilbao by foreign troops, I have to acknowledge my debt of gratitude to you for your efforts to make known the facts and to win the support of Great Britain in the relief of destitute women, children and old people who, in expiation of their refusal of a Fascist regime, have, for so many months, suffered the hardship and privation of civil war. I am glad of this opportunity to express, on behalf of the Government of Euzkadi and myself, our heartfelt thanks for the help which you have so graciously lent us and which I feel sure we may call upon at all times. Yours sincerely, (signed) José T. de Lizaso. Sir Walter Citrine, K.B.E. COPIED KMS/27.8.37. 292/946/11/75